2001
DOI: 10.1002/1521-3765(20011001)7:19<4280::aid-chem4280>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis through Disulfide Exchange: Discovery of Potent Psammaplin A Type Antibacterial Agents Active against Methicillin-ResistantStaphylococcus aureus (MRSA)

Abstract: Psammaplin A is a symmetrical bromotyrosine-derived disulfide natural product isolated from the Psammaplysilla sponge, which exhibits in vitro antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). Inspired by the structure of this marine natural product, a combinatorial scrambling strategy for the construction of heterodimeric disulfide analogues was developed and applied to the construction of a 3828-membered library starting from 88 homodimeric disulfides. These psammaplin A anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…The antibacterial and antifungal activities of the bromotyrosine alkaloids are summarized in Table IV and Table V Interestingly, Gram-positive bacteria are highly susceptible to purpuramine L when compared to the positive control kanamycin (122). Psammaplin A (152) was found to possess antimicrobial activity (109,254,255). It also selectively inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA) (256).…”
Section: A Antimicrobial Activitymentioning
confidence: 99%
“…The antibacterial and antifungal activities of the bromotyrosine alkaloids are summarized in Table IV and Table V Interestingly, Gram-positive bacteria are highly susceptible to purpuramine L when compared to the positive control kanamycin (122). Psammaplin A (152) was found to possess antimicrobial activity (109,254,255). It also selectively inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA) (256).…”
Section: A Antimicrobial Activitymentioning
confidence: 99%
“…Introduction of a bromine atom at 5 was carried out by reported method in 2 steps. 15) Di-brominated phenol (6) was treated with iodide (8), which was prepared from N-(3-hydroxyproyl)phthalimide (7), 18) in the presence of potassium carbonate (K 2 CO 3 ) and benzyltriethylammonium chloride (BTAC) provided ether (9) in high yields (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…Because of these interesting activities, a number of synthetic studies on these alkaloids have been reported. [6][7][8][9][10][11][12][13][14][15][16] Moloka'iakitamide (1) 17) has been isolated from the Red Sea sponge Pseudoceratina arabica (Pseudoceratinidae) and shows significant parasympatholytic effects on isolated rabbit heart and jejunum, and weakly antifungal activity, contains one bromotyrosine unit and oxalamide moiety (Fig. 1).…”
Section: Notesmentioning
confidence: 99%
“…This was fi rst demonstrated with a disulfi debased DCL using the pre -equilibrated approach [65] . Based on studies of the marine natural product psammaplin A, an antibacterial agent potent against methicillin -resistant Staphylococcus aureus ( MRSA ), a very large ditopic library composed of more than 3000 constituents was designed.…”
Section: Cellsmentioning
confidence: 99%